Considerations on water quality and the use of chlorine in times of SARS-CoV-2 (COVID-19) pandemic in the community (2020)
This review goal is to reflect on the challenges and prospects for water quality in the face of the pandemic caused by the new SARS-CoV-2 coronavirus (COVID-19). Based on the information available so far, the detection of SARS-CoV-2 RNA in wastewater has raised interest in using it as an early warning method, to detect the resurgence of infections and to report the risk associated with contracting SARSCoV-2 in contact with untreated water or inadequately treated wastewater is discharged. The wastewater-based epidemiological approach can be used as an early indicator of infection within a specific population. On the other hand, it is necessary to collect information from the managers of drinking water supply companies and professionals who are related to water quality, to know SARS-CoV-2 data and information, and its influence on drinking water quality. The basic purpose of this review article is to try to provide a valuable and quick reference guide to COVID-19. Important topics were discussed, such as detection of SARS-CoV-2 in wastewater in various parts of the world; wastewater screening to monitor COVID-19; persistence of SARS-CoV-2 in aquatic systems; the presence of SARS-CoV-2 in drinking water; clean water as a mechanism to deal with the COVID-19 pandemic; chlorine as a disinfectant to eliminate SARS-CoV-2 and damage to ecosystems by the use of chlorine. Currently does not exist extensive literature on the effectiveness of water and wastewater treatment processes that ensure the correct elimination of SARS-CoV2. Excessive use of disinfectants such as chlorine is causing effects on the environment. This document highlights the need for further research to establish the behavior of the SARS-CoV-2 virus in aquatic systems. This study presents an early overview of the observed and potential impacts of COVID-19 on the environment.